KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI SMP NEGERI 1 CANDIROTO, TEMANGGUNG - Murbaningtyas, Indriyanti; Nina Oktarina; Fathur Rokhman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This article describes descriptive qualitative research on the transformational leadership of school principals in improving the quality of education at SMP Negeri 1 Candiroto, Temanggung Regency, Central Java Province. Transformational leadership describes the role of a leader to bring about change in the environment he leads. Transformational leadership is characterized by having a clear and inspiring vision, the ability to motivate and inspire, a focus on individual development, and leadership based on values.. This research was carried out by means of interviews, observation and documentation. The aim of this research is to find out and understand the role of the principal's transformational leadership in improving the quality of education at SMP Negeri 1 Candiroto.